Coconut Oil: Nutrition and Health - Dayrit, Fabian M (Archīum Ateneo, 2024)
This chapter provides an overview of coconut oil as it is one of the most multi-functional vegetable oils, providing an efficient energy source for mitochondria, as well as therapeutic properties and antimicrobial activity. Virgin coconut oil has been shown in a clinical study to be effective in improving mild cases of coronavirus disease 2019 (COVID-19). There is positive evidence for its benefits for Alzheimer’s disease. Unfortunately, coconut oil has been erroneously identified with animal fats and margarines. Given its numerous health benefits and the absence of evidence regarding the link between coconut oil and heart disease, it is clear from the information presented in this chapter that the nutritional advice against coconut oil needs to be revisited.